Research in Integrated Health Care and Publication Trends from the Perspective of Global Informatics - Li, Zhong; Zhang, Liang; Pan, Zijin; Zhang, Yan (Das Gesundheitswesen, 2019)
Background Integrated care has gained popularity in recent decades and is advocated by the World Health Organization. This study examined the global progress, current foci, and the future of integrated care.Methods We conducted a scientometric analysis of data exported from the Web of Science database. Publication number and citations, co-authorship between countries and institutions and cluster analysis were calculated and clustered using Histcite12.03.07 and VOS viewer1.6.4.Results We retrieved 6127 articles from 1997 to 2016. We found the following. (1) The United States, United Kingdom, and Canada had the most publications, citations, and productive institutions. (2) The top 10 cited papers and journals were crucial for knowledge distribution. (3) The 50 author keywords were clustered into 6 groups: digital medicine and e-health, community health and chronic disease management, primary health care and mental health, healthcare system for infectious diseases, healthcare reform and qualitative research, and social care and health policy services.Conclusions This paper confirmed that integrated care is undergoing rapid development: more categories are involved and collaborative networks are being established. Various research foci have formed, such as economic incentive mechanisms for integration, e-health data mining, and quantitative studies. There is an urgent need to develop performance measurements for policies and models.
Keywords: integrated care; collaboration network; research trends; knowledge map